Theoretical-methodological, practical problems of financial accounting in enterprises and directions for improving audit - Allahyarov, Rauf (Technium Social Sciences Journal, 2023)
Recently, much attention has been paid to the unification of accounting at the international level. The growing role of international integration in various sectors of the economy requires the harmonization of accounting and reporting practices in different countries and their transparency. The paper analyzes different theoretical-methodological, practical problems of financial accounting in enterprises. Furthermore, different mechanisms and concepts have been determined that influencing the financial relations of the country. Oil and gas reserves are one of the key factors in Azerbaijan's economy, cultural development and improving the socio-cultural welfare of the population. Financial management of oil and gas industry in Azerbaijan has been chosen for identifying the main directions of the audit system. SOCAR and SOFAZ are the significant company that enhance Azerbaijan’s economy by importing and exporting oil and gas worldwide. The reason why SOCAR has been selected for investigating is the company’s aim focuses on ensuring the fuel and energy security of the Republic of Azerbaijan. At the same time, due to the growing financial resources of the country, trategic infrastructure projects of international importance are being successfully implemented, which create conditions for the modernization of transport infrastructure not only in Azerbaijan but in the region as a whole.